2020
DOI: 10.3390/electronics9091523
|View full text |Cite
|
Sign up to set email alerts
|

Bagged Tree Based Frame-Wise Beforehand Prediction Approach for HEVC Intra-Coding Unit Partitioning

Abstract: High Efficiency Video Coding (HEVC) has achieved about 50% bit-rates saving compared with its predecessor H.264 standard, while the encoding complexity increases dramatically. Due to the introduction of more flexible partition structures and more optional prediction directions, HEVC takes a brute force approach to find the optimal partitioning result which is much more time consuming. Therefore, this paper proposes a bagged trees based fast approach (BTFA) and focuses on the coding unit (CU) size decision for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…To further analyze the coding performance of the proposed algorithm, we compare it with three recent studies. Respectively, they are convolution neural network-based fast algorithm (CNNFA) proposed by Liu et al [18], fast intra-CU splitting algorithm (FICUSA) proposed by Zhong et al [30], and bagged tree-based fast algorithm (BTFA) proposed by Li et al [31]. CNNFA, FICUSA, and BTFA are all effective schemes for intra-CU size decision of HEVC, and their performance on standard test sequences is listed in Table 3.…”
Section: Encoding Performancementioning
confidence: 99%
“…To further analyze the coding performance of the proposed algorithm, we compare it with three recent studies. Respectively, they are convolution neural network-based fast algorithm (CNNFA) proposed by Liu et al [18], fast intra-CU splitting algorithm (FICUSA) proposed by Zhong et al [30], and bagged tree-based fast algorithm (BTFA) proposed by Li et al [31]. CNNFA, FICUSA, and BTFA are all effective schemes for intra-CU size decision of HEVC, and their performance on standard test sequences is listed in Table 3.…”
Section: Encoding Performancementioning
confidence: 99%
“…These feature candidates are from four fields, which are information from neighboring CTUs, side information during pre-encoding process, statistical information of CTU pixels and information from pixel filtering results. We will give a brief introduction of these feature candidates in the following paragraphs, and more details are available in our previous work [32]. Results of [33] suggested that information from neighboring CTUs is useful for the partition decision making of current CU.…”
Section: Features Design For Bagged Tree Modelmentioning
confidence: 99%
“…Many existing works have developed numbers of useful attributes for CU splitting label prediction. Based on these existing features, in our previous work [32] we also designed several novel features proven to be effective. As a result, based on our particular task of this paper we select totally 29 feature candidates used in [32], and they are listed in Table I along with corresponding meanings.…”
Section: Features Design For Bagged Tree Modelmentioning
confidence: 99%
See 2 more Smart Citations